Assessment of utilization factor in network over the growth of photovotlaic system - Loo, Pin Likh (2020)
There are several potential benefits of the installation of distributed generation unit such as photovoltaic system. In order to acquire full advantage of photovoltaic system, it has to integrate optimally sized appropriate of renewable energy generation at locations. With a joint of lowering the greenhouse gas emissions and dependency of fossil fuels, the global now urges to shift toward lowcarbon economies. The potential of distributed generation could lead many opportunities in term of economies, environ ment, technologies, and the future research purpose. In addition, this paper analyses the growth of photovoltaic system that may attract to the conflict of interests, economies, and technique issues on penetration of photovoltaic system to the network. By increasing the photovoltaic system in network over the years, the installation could provoke the power quality and operation issues. Therefore, optimization tools are applied for optimizing the distributed generation in the network. Finally, it concludes t hat optimization power flow and analytical approach is used for analyzing the growth of photovoltaic system to the network. The proposed approach is implemented to simulate the assumption data and the simulation results are carried out.